Back Cover: Palladium‐Catalyzed Cross‐Dehydrogenative Functionalization of C(sp2)H Bonds (Chem. Asian J. 1/2014). Issue 1 (January 2014) - Wu, Yinuo; Wang, Jun; Mao, Fei; Kwong, Fuk Yee
<x xml:space="preserve">Abstract</x> Dehydrogenation An attractive feature of catalytic cross‐dehydrogenative coupling (CDC) reactions is the formation of a CC bond from two CH moieties under oxidative conditions. In their Focus Review on page 26 ff., Jun Wang, Fuk Yee Kwong et al. highlight recent advancements in palladium‐catalyzed C(sp2)C(sp2) bond formation through a dehydrogenative pathway. With the rocket‐like power catalyst system (i.e., palladium/ligand/oxidant), a variety of C(sp2)H bonds can be effectively zipped up through the expelling of H2‐[oxidant].<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>